Phosphate speciation on Al-substituted goethite: ATR-FTIR/2D-COS and CD-MUSIC modeling. Issue 12 (23rd October 2019) - Xu, Jinling; Koopal, Luuk K.; Wang, Mingxia; Xiong, Juan; Hou, Jingtao; Li, Yan; Tan, Wenfeng
Abstract : Natural goethite commonly encounters Al substitution for Fe, which alters the surface reactivity of goethite. Abstract : Natural goethite commonly encounters Al substitution for Fe, which alters the surface reactivity of goethite. Whether and how Al substitution affects the surface speciation of phosphate remain poorly understood. Therefore, the phosphate adsorption and speciation of Al-substituted (6 and 9 mol%) goethite were investigated by combining attenuated total reflectance Fourier transform infrared (ATR-FTIR) and CD-MUSIC modeling. Al substitution caused a decrease in the crystal length-to-width ratio of goethite and the ratio of (110)/(021) faces was estimated to be 90/10, 85/10 and 81/19 for goethite with about 0, 6 and 9 mol% Al, respectively. The decreasing (110)/(021) face ratio and increasing surface roughness with increasing Al substitution enhanced the surface charge density and phosphate adsorption capacity of goethite. Two-dimensional correlation spectroscopy (2D-COS) analysis showed that three types of phosphate complexes were formed on both pure and Al-substituted goethites. CD-MUSIC modeling, based on electron microscopy and ATR-FTIR results to arrive at some of the parameters, could describe both the proton and the phosphate adsorption well with optimized remaining parameters. The model parameters indicated that Al substitution in goethite led to larger affinity constants for bidentate phosphate complexes and smaller values for monodentate complexes. Therefore, a larger percentage of bidentate phosphate complexes were formed on Al-substituted goethite than on pure goethite. Monodentate phosphate complexes were hardly formed on the Al sites of Al-substituted goethite. The results improve our insight regarding phosphate binding to Al-substituted goethite and phosphorus availability and mobility in iron-rich soils.